Anchored hearts - Oliveras, Priscilla (Oliveras, Priscilla. Keys to love., 2021)
An award-winning, globe-trotting photographer returns home to Key West after being sidelined with an injury requiring a long recuperation and tries to reconnect with the girl he left behind.